2011
DOI: 10.1063/1.3592997
|View full text |Cite
|
Sign up to set email alerts
|

Do droplets always move following the wettability gradient?

Abstract: Impacting droplets on rough surfaces with a wettability gradient have been reported to rebound obliquely or migrate following the wettability gradient due to the unbalanced interfacial forces created by such heterogeneous architectures. Here we demonstrate under certain conditions, droplets can be self-propelled against the wettability gradient. We show that the local Cassie-to-Wenzel transition in the droplet is critical for such a counter-intuitive phenomenon. We believe that our letter extends our conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 19 publications
4
63
1
Order By: Relevance
“…It is reported that the contact time in the case of the oblique impact is basically the same as that of the vertical impact . On another note, oblique bouncing can also occur on the horizontally placed surface but a wetting or thermal gradient …”
Section: Introductionmentioning
confidence: 92%
“…It is reported that the contact time in the case of the oblique impact is basically the same as that of the vertical impact . On another note, oblique bouncing can also occur on the horizontally placed surface but a wetting or thermal gradient …”
Section: Introductionmentioning
confidence: 92%
“…By engineering nonuniform textures to create roughness gradients on the substrate, Wang and co‐workers achieved a gradient surface, where the droplet can be controlled to rebound axially and rebound by a prescribed lateral trajectory . Additionally, they found that, different from the previous reports, the self‐migration direction (toward or against the wettability gradient) mainly depended on the competition of the capillary pressure and the effective water hammer pressure . This is significant for some potential applications, such as antifogging, water‐harvesting, and anti‐icing.…”
Section: The Mechanisms Of Anti‐icing and Icephobicitymentioning
confidence: 98%
“…Notably, when a droplet bounces on the substrate, how to control the direction is vital to the transportation of the droplets . Using the decorated substrates with a texture of variable density, Quéré and co‐workers investigated the impacting water drops bouncing off obliquely.…”
Section: The Mechanisms Of Anti‐icing and Icephobicitymentioning
confidence: 99%
See 1 more Smart Citation
“…These control parameters include wettability of the surface, surface tension, impact velocity of the droplet, liquid density, liquid viscosity, and surface roughness. [1][2][3][4][5][6][7][8][9][10] Understanding the behaviors of droplets impacting a nanostructured solid surface plays an important role in industrial and environmental processes, such as spray cooling, ink-jet printing, and deposition of rain on solid surfaces. 11 Droplets that impact a textured solid surface immediately spread at the moment of impact.…”
mentioning
confidence: 99%